The production and characterisation of inorganic combinatorial libraries - Karimi, O. (Cranfield University, 2010)
With the increasing demand for research into new materials, techniques which are able to produce and characterise a large number of samples rapidly are becoming indispensable. Thin film technology has the potential to improve the amount of information contained on deposited samples by creating compositionally graded libraries. Conventionally, raster scan methods are used to interrogate such libraries. The production of combinatorial samples by methods not previously employed in this role has been carried out. Both solution based electrochemical deposition and electrostatic spray vaporisation production methods have been successfully modified to produce thin film continuous compositional spread (CCS) samples. Additional samples have been produced by off-axis direct current magnetron sputtering, a method already established in the combinatorial field. Presented here is a different approach to provide high-throughput data collection and analysis of combinatorial libraries using an X-ray diffraction (XRD) probe. An extended X-ray beam was used to illuminate the polycrystalline libraries and a large area detector used to collect the data. A new partitioning algorithm has been employed to analyze the collected data and extract the crystallographic information from the illuminated area. The results of the technique have been compared with the raster scans showing that the algorithm provides reliable data equivalent to multiple point data collections with significantly increased data acquisition speed. With the new chemical libraries and other simplified samples the partitioning method has been shown to be appropriate for the analysis of both distinct composition high density chemical libraries and also CCS samples. To achieve the validation of the new method the new libraries have been illumination with the extended beam X-ray source. The resultant superimposed diffraction patterns are partitioned with the novel software and compared with conventional XRD. The resolution of the partitioning method has been shown to be in the 1 mm range when applied to CCS libraries and 1.5 mm for high density chemical libraries. For randomly orientated polycrystalline samples the d-spacing change between the partitioned data and the corresponding raster scanned data is not statistically significant. This corresponds to d-spacing determination with a precession of < 0.01 Å when used with the Bruker D8 diffractometer and our geometry.